Does Earnings Management Moderate the Effects of Profitability, Capital Structure, and Accounting Conservatism on Firm Value? - Limbong, Diamond; Astriwati, Astriwati; Musa, Marsuddin; Maimuna, Yuni (E-Jurnal Akuntansi; Vol 34 No 7 (2024), 2024)
The value of a firm as a form of achievement that will impact investor and public trust. Firm value is often considered as one of the most accurate indicators in measuring the well-being of shareholders. This research aims to analyze the influence of profitability, capital structure, and accounting conservatism on firm value, with earnings management as a moderating variable. The data for this research is quantitative and obtained through the annual reports of the 20 largest banks in ASEAN from 2019 to 2022. The data analysis method used in this research includes multiple linear regression tests and moderate regression analysis. The results of this research indicate that profitability and capital structure have a significant negative impact on the firm value. Earnings management has a significant positive impact on the firm value. Meanwhile, accounting conservatism does not have a significant impact on firm value. The moderation test shows that the earnings management variable is able to strengthen the influence of profitability, capital structure, and accounting conservatism variables on firm value. Thus, earnings management is considered appropriate as a moderating variable in this research. Keywords: Profitability; Capital Structure; Accounting Conservatism; Earnings Management;Firm Value